SGLT2 inhibitors in preventing progression of chronic kidney disease in patients with type 2 diabetes: a literature review - Szczepański, Michał; Kuliga, Marcin; Bajak, Mateusz; Słowik, Julia; Inglot, Julia; Inglot, Jadwiga; Feret, Dominik Maciej; Zapasek, Daniel; Mamczur, Maciej; Sowa, Damian (Journal of Education, Health and Sport, 2024)
Introduction Type 2 diabetes mellitus (T2DM) is an increasing health concern, and diabetic kidney disease (DKD) affects 30–40% of patients with diabetes. Sodium-glucose cotransporter 2 inhibitors (SGLT2i) are effective medications used in the treatment of T2DM, which not only improve glycemic control but also slow the progression of diabetic kidney disease (DKD), reducing the risk of renal and cardiovascular complications. They work by decreasing glomerular hyperfiltration and alleviating inflammation in the kidneys. Clinical studies have demonstrated significant therapeutic benefits, including a reduction in albuminuria and improvement in renal function. In the future, the development of new drug classes, such as Nrf2 activators and RAS inhibitors, which are currently under clinical investigation, may further advance the treatment of DKD, offering a more personalized approach to therapy. This article reviews the current knowledge on SGLT2i and their impact on the progression of DKD, the future prospects for therapies in managing diabetes and its complications. Aim of the Study: The aim of this study was to gather and analyze available scientific publications regarding the effect of sodium-glucose cotransporter 2 inhibitors (SGLT2i) on slowing the progression of chronic kidney disease (CKD) in patients with T2DM and to determine the future of therapy based on new reports and research into emerging drug classes. Materials and Methods: We conducted a review and analysis of the literature available in the PubMed database, using keywords such as SGLT2 inhibitors, gliflozins, chronic kidney disease, type 2 diabetes.